2019
DOI: 10.1002/jbmr.3697
|View full text |Cite
|
Sign up to set email alerts
|

A Metabolic Screen in Adolescents Reveals an Association Between Circulating Citrate and Cortical Bone Mineral Density

Abstract: Observations that insulin and adiponectin levels are related to cortical bone size in adolescents, independently of body composition, suggest factors related to fat metabolism directly influence skeletal development. To explore this question, we examined associations between a metabolic screen focusing on fat metabolism, and peripheral quantitative computed tomography (pQCT) measures of the mid‐tibia, in 15‐year‐olds from the Avon Longitudinal Study of Parents and Children. Metabolic profiles were generated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Human osteoblasts can produce citrate; it is hypothesized that citrate is incorporated into bone directly from osteoblast secretion, and that, as bone is resorbed and both bone collagen and mineral are degraded, citrate is released into the circulation generating the major source of plasma citrate . This concurs with the positive relationships we observed between citrate and both age and bone resorption and an inverse association recently identified between β‐CTX and citrate in a smaller sample from the ALSPAC adolescent population . Due to its suggested association with bone mineral, we hypothesize that plasma citrate may provide information on turnover of bone mineral during bone resorption.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Human osteoblasts can produce citrate; it is hypothesized that citrate is incorporated into bone directly from osteoblast secretion, and that, as bone is resorbed and both bone collagen and mineral are degraded, citrate is released into the circulation generating the major source of plasma citrate . This concurs with the positive relationships we observed between citrate and both age and bone resorption and an inverse association recently identified between β‐CTX and citrate in a smaller sample from the ALSPAC adolescent population . Due to its suggested association with bone mineral, we hypothesize that plasma citrate may provide information on turnover of bone mineral during bone resorption.…”
Section: Discussionsupporting
confidence: 92%
“…25 This concurs with the positive relationships we observed between citrate and both age and bone resorption and an inverse association recently identified between β-CTX and citrate in a smaller sample from the ALSPAC adolescent population. 26 Due to its suggested association with bone mineral, we hypothesize that plasma citrate may provide information on turnover of bone mineral during bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…The weight percentages of the different metabolic acids in the bone vary according to animal age: fetal bone, which is much softer than adult bone, contains very large quantities of lactate, [32] whereas in adult bone, the quantity of citrate is directly related to bone mineral quality. [33] Currently, the role and characterization of metabolic acids in the bone is very poorly understood as well as their underlying role in biomineralization.…”
mentioning
confidence: 99%
“…The roles of citrate and lactate in bone mineral structure have been much less studied than those of carbonate. In adult humans, bone mineral density correlates positively with the concentration of blood plasma citrate, 12 whilst foetal bone, which is typically much softer than mature bone, contains considerable quantities of lactate. 13 We have shown that the citrate chemical environment in bone is similar to that in octacalcium phosphate (OCP)-citrate by SSNMR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%